Biodistribution of the boron carriers boronophenylalanine (BPA) and/or decahydrodecaborate (GB-10) for Boron Neutron Capture Therapy (BNCT) in an experimental model of lung metastases - Trivillin, Verónica Andrea (2013)
BNCT was proposed for the treatment of diffuse, non-resectable tumors in the lung. We performed boron biodistribution studies with 5 administration protocols employing the boron carriers BPA and/or GB-10 in an experimental model of disseminated lung metastases in rats. All 5 protocols were non-toxic and showed preferential tumor boron uptake versus lung. Absolute tumor boron concentration values were therapeutically useful (25–76 ppm) for 3 protocols. Dosimetric calculations indicate that BNCT at RA-3 would be potentially therapeutic without exceeding radiotolerance in the lung.